2016
DOI: 10.3208/jgssp.chn-49
|View full text |Cite
|
Sign up to set email alerts
|

The field test for influence of ram-compacted piles with bearing base on settlement of embankments in China Beijing-Shanghai high-speed railway on deep soft soil

Abstract: The stratums along the Beijing-Shanghai high-speed railway are composed mainly with soft soil. The foundation of roadbed were strengthened in hope of reducing differential and total settlement. Ram-compacted piles are mentioned in this paper, as an example of strengthening methods. Using joint test method combining liquid level settlement gauges and single point settlement gauges, total settlements and compressions at different depths were measured. Field test results showed that:1. The settlements were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Under this background, an innovative construction technique named ram-compacted piles with vibrating gravel base was invented in soft clay areas which can effectively reinforce foundation of industrial and civil architecture, even that of railway engineering. According to the statistics of field tests conducted by Ma [3], ram-compacted piles with vibrating gravel base is capable to reduce settlement of roadbed in soft soil areas efficiently. What is more, a series of research by Chen [4] indicated that the improvement of properties of adjacent soil surrounding piles can increase ultimate bearing capacity of foundation apparently.…”
Section: Introductionmentioning
confidence: 99%
“…Under this background, an innovative construction technique named ram-compacted piles with vibrating gravel base was invented in soft clay areas which can effectively reinforce foundation of industrial and civil architecture, even that of railway engineering. According to the statistics of field tests conducted by Ma [3], ram-compacted piles with vibrating gravel base is capable to reduce settlement of roadbed in soft soil areas efficiently. What is more, a series of research by Chen [4] indicated that the improvement of properties of adjacent soil surrounding piles can increase ultimate bearing capacity of foundation apparently.…”
Section: Introductionmentioning
confidence: 99%